2020
DOI: 10.1017/s0022029920000503
|View full text |Cite
|
Sign up to set email alerts
|

Early weaning: new insights on an ever-persistent problem in the dairy industry

Abstract: It is common practice in the dairy industry to separate the calf from the cow immediately after parturition, and in most parts of the world calves are housed individually during the milk-feeding period. Early and abrupt separation has major implications for the calf's physical and psychological development. In this Research Reflection short review we present and discuss the main housing systems and management practices regarding early weaning in today's dairy industry. Main benefits and disadvantages are criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 41 publications
(65 reference statements)
0
20
0
Order By: Relevance
“…Previous studies with calves have demonstrated that decreasing the milk allowance during the artificial milk feeding period or optimizing the type of solid feed (e.g., presentation form and taste) and feeder location prior to weaning can encourage young ruminants to increase the solid feed intake ( 1 , 4 ). However, artificial milk feeding in conjunction with early weaning strategies can limit the rumen microbiological colonization by a microbial consortium able to perform the major fermentative and metabolic functions required at weaning and beyond, which may have negative effects on the weaning process ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies with calves have demonstrated that decreasing the milk allowance during the artificial milk feeding period or optimizing the type of solid feed (e.g., presentation form and taste) and feeder location prior to weaning can encourage young ruminants to increase the solid feed intake ( 1 , 4 ). However, artificial milk feeding in conjunction with early weaning strategies can limit the rumen microbiological colonization by a microbial consortium able to perform the major fermentative and metabolic functions required at weaning and beyond, which may have negative effects on the weaning process ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Weaning of ruminants in natural conditions is a progressive process that occurs between 6 and 9 months of age, and it is characterized by a decrease in the frequency of suckling, with an increase in the frequency and amount of solid feed intake and development of more complex social interactions ( 1 ). However, in the current dairy production systems ruminants are weaned much earlier and newborns are typically separated from their dams immediately or during the first hours after birth, and they have no contact with adult ruminants until they are weaned or later.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these advantages, dairy farmers are reluctant to adopt group housing due to concerns over more difficult handling and health monitoring (Rushen et al, 2008), cross-sucking, aggression (reviewed by Costa et al, 2016), and disease transmission (Webster et al, 1985;Gulliksen et al, 2009;Curtis et al, 2016). Pair housing of calves could be an attractive option for farmers because it combines the benefits of social contact with the practical advantages of easy handling and illness monitoring (Mikuš et al, 2020), as well as limits the number of nose-nose and fecal-oral contacts responsible for the transmission of enteric and respiratory diseases (McGuirk, 2008). Moreover, many of the positive effects of group housing on the behavior and welfare of calves could be also achieved by pair housing.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the challenges with raising calves separated from their dams are commented on by Mikuš et al . (2020) and Relić et al . (2020) in the last two papers in the previous section of this issue.…”
mentioning
confidence: 95%